2019
DOI: 10.1038/s41598-018-36554-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Carbapenem Resistant Klebsiella pneumoniae and Klebsiella quasipneumoniae Isolated from Lebanon

Abstract: Klebsiella pneumoniae is a Gram-negative organism and a major public health threat. In this study, we used whole-genome sequences to characterize 32 carbapenem-resistant K. pneumoniae (CRKP) and two carbapenem-resistant K. quasipneumoniae (CRKQ). Antimicrobial resistance was assessed using disk diffusion and E-test, while virulence was assessed in silico. The capsule type was determined by sequencing the wzi gene. The plasmid diversity was assessed by PCR-based replicon typing to detect the plasmid incompatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 61 publications
9
46
0
Order By: Relevance
“…The results shown in Table 1 indicate that in Lebanon, during 2020 through 2020, resistance to 3rd- and 4th-generation cephalosporins, such as cefotaxime, ceftazidime, and cefepime, aminoglycosides, e.g., gentamicin and amikacin, ciprofloxacin—a quinolone drug—and carbapenems, such as imipenem and meropenem, was higher. Curiously, resistance to piperacillin-tazobactam was relatively lower [ 77 , 78 , 79 , 80 ]. The increasing antibiotic resistance trends in Lebanon were justified by characterization of β-lactamase phenotypic and genotypic activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shown in Table 1 indicate that in Lebanon, during 2020 through 2020, resistance to 3rd- and 4th-generation cephalosporins, such as cefotaxime, ceftazidime, and cefepime, aminoglycosides, e.g., gentamicin and amikacin, ciprofloxacin—a quinolone drug—and carbapenems, such as imipenem and meropenem, was higher. Curiously, resistance to piperacillin-tazobactam was relatively lower [ 77 , 78 , 79 , 80 ]. The increasing antibiotic resistance trends in Lebanon were justified by characterization of β-lactamase phenotypic and genotypic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular analysis carried with PCR, shown in Table 2 indicated that bla SHV , bla TEM and bla CTX-M were the most predominant ESBL-encoding genes among E. coli and ESKAPE pathogens, this increasing trend was also observed for bla OXA , and bla GES ESBL traits. On the other hand, bla VIM was the most common metallo-β-lactamass resistance encoding gene which showed remarkable increase, with fewer isolates shown to express the bla NDM ESBL trait [ 77 , 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the molecular epidemiological characteristics of CR-ECL infection are different from region to region. 13,14 In this study, we attempted to systematically analyse the epidemiological characteristics of CR-ECL infection to provide evidence for effective control of nosocomial infection with CR-ECL.…”
Section: Introductionmentioning
confidence: 99%
“…We first report the high presence of co-existing carbapenem-resistant genes bla KPC-2 (71%), bla NDM-1 (25%) with ESBLs encoding gene in Shenzhen, China as well co-existence of carbapenem resistance genes in ESBLs-producing K. pneumoniae has flagged concern about the spread of such superbugs in the Shenzhen area. Several reports have shown the co-existence of carbapenem resistance genes and ESBLs encoding genes in K. pneumoniae on a global scale [21]. Our MLST results demonstrated that ST20 and ST2407 were highly prominent in Shenzhen area which encodes ESBLs genes.…”
Section: Discussionmentioning
confidence: 54%